Potential of microalgae Tetraselmis Chuii as feedstock for biodiesel application - Kumaran P.; Saifuddin N.; Janarthanan S. (Praise Worthy Prize, 2023)
Biodiesel production from microalgae has attracted major interest recently as a renewable energy which is capable of reducing the effect of global warming at same time provide sustainable energy source. This study determines the potential of microalgae species, Tetraselmiss chuii lipid as a biodiesel feedstock. Fatty acid profiling of the biodiesel, obtained from T.chuii lipid showed higher content of saturated fatty acids (SFA) 50.1% than monounsaturated fatty acids (MUFA) 31.6% and polyunsaturated fatty acids (PUFA) 17.5%. The biodiesel produced was also characterized in terms of kinematic viscosity, cetane number, iodine value, degree of unsaturation and higher heating value. The quality of the biodiesel produced from T.chuii lipid were a kinematic viscosity of 3.2 mm2/s, a cetane number of 63.7, an iodine value of 59.3 g I2/ 100g-1, a degree of unsaturation of 66.6% and a higher heating value of 41.3 MJ/kg. The result obtained from this study indicated that the biodiesel produced from T.chuii lipid complies with the US Standard (ASTM 6751) and European Standard (EN14214). © 2014 Praise Worthy Prize S.r.l. - All rights reserved.